Current concepts of tocilizumab efficacy in active moderate-to-severe corticosteroid-resistant cases of Graves’ orbitopathy - Boutzios, Georgios; Nikolopoulou, Anastasia; Chatzi, Sofia; Tzioufas, Athanasios G.; Goules, Andreas V. (Frontiers in Endocrinology, 2025)
Graves’ orbitopathy (GO) is an autoimmune disease affecting the orbit and the retro-ocular tissues. GO pathogenesis involves multiple complex mechanisms, including the contribution of many inflammatory cytokines, such as interleukin-6 (IL-6). GO severity ranges from mild to severe and sight-threatening cases, with the latter affecting only a small percentage of patients. A considerable number of these patients do not respond to first-line immunosuppressive therapy with weekly intravenous pulses of corticosteroids and therefore, there is an unmet need for a second-line treatment, based on immunosuppressive drugs. In recent years tocilizumab (TCZ), an IL-6 inhibitor, has emerged as an effective and safe alternative option for the treatment of active, moderate-to-severe, refractory to steroids cases of GO. This review focuses on the up-to-date concepts regarding TCZ administration for the management of these patients.